Pembelajaran Literasi Membaca Siswa Sekolah Dasar Kelas I - Ahmad Syarif (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2021)
This study aims to understand deeply the learning of literacy reading in elementary school class I. The research problem is based on the low student interest in learning, low literacy reading skills, and the teacher is too focused on the 2013 curriculum without facilitating student needs. The research method uses a qualitative approach to the design of phenomenology with the stages of essence deepening, variations in imagination, and reduction of phenomenology. The time and place of the study were conducted at Cijambu Elementary School in Elementary School I class, located at Jln Cigombong Station, Bogor Regency. The study was conducted for six months. The results were obtained that reading literacy learning uses Curriculum 2013 with the aim of reading comprehension. Learning media use word cards and learning strategies use the phonic approach for those who cannot read and the direct approach for those who have mastered phonemic awareness. Evaluation of learning is carried out formally according to the curriculum without an innovation development in the form of literacy assessment. Recommendations namely, this research should be developed in other aspects of language to be more comprehensive. Keywords: Learning, Reading Literacy, Grade I Students